군 병사의 군 생활스트레스와 군 생활적응과의 관계에서 대인관계능력의 조절효과 - 김세원(Se-Won Kim); 신창식(Chang-Sik Shin) (한국콘텐츠학회 논문지, 15(7), 2015)
The purpose of this study is to investigate the moderating effect of interpersonal relationship skills in adapting military life and stress in the army. For this purpose, 453 soldiers in Chungnam and Daejeon were surveyed. First, the main result of this study is the difference in interpersonal skills and group life adjustment in accordance with the rank and class of the soldiers. Second, too much stress can cause difficulty to adapt military life and interpersonal skills. Also high interpersonal skills can help to adjust well to military life. Third, according to the survey, it was confirmed that the openness in the sub-factors of military life and military life stress was effective. This study suggests that it is important to help control the stress of military life to improve the ability of the openness of interpersonal skills in order to increase the adaptability military life. 본 연구는 군 병사의 군 생활스트레스와 군 생활적응 관계에서 대인관계능력의 조절효과를 알아보기 위한 것이다. 이를 위해 충남과 대전지역의 군 병사를 대상으로 설문조사를 하여 최종 453명을 분석하였다. 본 연구의 주요결과는 첫째, 군 병사의 계급과 병과에 따른 대인관계능력과 군 생활적응의 차이가 있음을 알 수 있었다. 둘째, 군 생활스트레스가 높으면 대인관계능력은 낮아지고 군 생활적응도 힘들어지며, 군 병사의 대인관계능력이 높을수록 군 생활적응을 잘 하는 것으로 나타났다. 셋째, 군 생활스트레스와 군 생활적응간의 관계에서 대인관계능력의 조절효과를 검증한 결과 대인관계능력의 하위요인 중 개방성에서 조절효과가 있음을 확인할 수 있었다. 본 연구는 군 병사의 군 생활스트레스를 조절하여 군생활적응력을 높이기 위해서는 대인관계능력 중 개방성의 능력을 향상시킬 수 있도록 돕는 것이 중요함을 시사한다.